Blue Urbanism: An Insight of Navigating Climate Change in Humid Tropical Cities in Brunei Darussalam - Yong, Gabriel Yit Vui; Hassan, Noor Hasharina (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2024)
Coastal cities are most at risk to rising sea levels and increased precipitation. This is however the Climate Change Scenario forecasted for the humid tropical region in the IPCC’s Sixth Assessment report. As standard engineering (grey) solutions are prohibitive in many developing countries due to financial and technical limitations, this paper proposes an adaptive blue approach. It shares insights from Brunei, where the old capital was a city built over water. It also presents findings from a preliminary survey to gauge the public’s views on a set of blue urbanism proposals. The study found positive support for the proposals in general. In particular, there was strong support for: (i) incorporating ‘green’ features into the urban complex; (ii) more public spaces where people could learn about their cultural heritage; and (iii) participation in the life and management of the city. There is however (iv) less enthusiastic response to blue features. The paper discusses viability of the blue urbanism approach vis-à-vis cultural and contextual changes. The insights presented could be useful to other coastal cities in the region.